Sources of software development task friction - Bradley, Nick C.; Fritz, Thomas; Holmes, Reid (Empirical software engineering : an international journal, 2022)
Given a task description, a developer’s job is to alter the software system in a way that accomplishes the task, usually by fixing a bug or adding a new feature. Completing these tasks typically requires developers to use multiple tools, spanning multiple applications, within their environment. In this paper, we investigate how existing desktop environments align with and facilitate developers’ needs as they tackle their tasks. We examine how developers use their tools to perform their tasks and the ways in which these tools inhibit development velocity. Through a controlled user study with 17 subjects and a field study with 10 industrial engineers, we found that developers frequently formulate specific objectives, or goals, on-demand as they encounter new information when progressing through their tasks. These goals are often not achievable directly in the environment, forcing developers to translate their task into goals and their goals into the low-level actions provided by the environment. When carrying out these low-level actions, developers routinely perform extra work such as locating and integrating resources and adapting their needs to align with the capabilities of the environment. This extra work acts as a form of friction, limiting how quickly and directly developers can complete their tasks. Much of this extra work exists due to mismatches between current tools and environments and how developers actually work in practice. This work identifies seven types of development friction and provides design recommendations that future tools and environments could use to more effectively help developers complete their tasks.